The Impact of a Multiple Conviction Record on Hiring Outcomes - Leasure, Peter (Crime & delinquency, 2021)
The objective of the current study was to examine the impact of a multiple conviction criminal record with varying crime types on hiring outcomes. An experimental correspondence audit was used to achieve this objective. The results showed that those with multiple conviction records and varying crime types received significantly fewer callbacks for interviews than those with no record. While the callback point estimates for those with this type of criminal history were not as low as expected, their statistically significant differences from those with no record were consistent with the bulk of previous research. The results also indicated the continued presence of racial discrimination in hiring practices as equally qualified African American applicants received significantly fewer callbacks than White applicants.